2008
DOI: 10.1188/08.onf.e53-e61
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise in Combination With Epoetin Alfa During High-Dose Chemotherapy and Autologous Peripheral Blood Stem Cell Transplantation for Multiple Myeloma

Abstract: Purpose/Objectives-To determine the effect of aerobic and strength resistance training and epoetin alfa (EPO) therapy on transfusions, stem cell collections, transplantation recovery, and multiple myeloma treatment response. Design-Randomized clinical trial.Setting-A myeloma research and therapy center in the south central United States.Sample-135 patients with multiple myeloma, 120 evaluable.Methods-Random assignment to exercise or usual care groups. All patients received EPO based on an algorithm. Aerobic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
65
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 22 publications
3
65
1
1
Order By: Relevance
“…Only two included a large population sample (nX100). 39,40 Nine studies (comprising 13 publications) were of high quality. 39,40,[52][53][54][58][59][60][61][62][63][64][65] Several exercise interventions for HSCT survivors took place during hospitalization 56,58,63 or started during hospitalization and continued after release, 40,57,[59][60][61][62]64 whereas others were performed only in the outpatient or homebased setting.…”
Section: Adultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Only two included a large population sample (nX100). 39,40 Nine studies (comprising 13 publications) were of high quality. 39,40,[52][53][54][58][59][60][61][62][63][64][65] Several exercise interventions for HSCT survivors took place during hospitalization 56,58,63 or started during hospitalization and continued after release, 40,57,[59][60][61][62]64 whereas others were performed only in the outpatient or homebased setting.…”
Section: Adultsmentioning
confidence: 99%
“…39,40,[52][53][54][58][59][60][61][62][63][64][65] Several exercise interventions for HSCT survivors took place during hospitalization 56,58,63 or started during hospitalization and continued after release, 40,57,[59][60][61][62]64 whereas others were performed only in the outpatient or homebased setting. 39,[52][53][54][55]65,66 Many interventions were aerobic and successfully increased functional capacity or at least offset the loss of functional capacity associated with HSCT. 40,52,55,57,61,66 Not surprisingly, there is substantial interest in the ability of physical activity interventions to change blood markers in HSCT patients, with inconclusive results to date.…”
Section: Adultsmentioning
confidence: 99%
See 2 more Smart Citations
“…7 Since this review, six new randomized controlled trials have been published, supporting these findings; some studies showed strong effects for body composition as well as weaker but promising effects for cardiorespiratory fitness, fatigue, muscle strength, physical functioning and quality of life. [8][9][10][11][12][13] Nevertheless, many questions remain unanswered regarding exercise interventions in HCT patients. Additional evidence is required to determine the optimal exercise recommendation, with respect to amount, type, intensity and time point for intervention.…”
Section: Introductionmentioning
confidence: 99%